Editorial - RAMOS HOLGUÍN, BERTHA; Peñaloza, Anna Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In Enletawa Journal we have been fortunate to come out of strong professional networks that have nourished us over the years. Thanks to all the reviewers and authors that have worked with us over the past several years, we have been able to flourish as an academic journal that presents articles of teachers who have realized that writing is a possibility to act autonomously and echo their voices in the development of the pedagogical experience. In this volume, we share stories from diverse corners of Colombia. Thanks to the many teachers who care about their students and who work tirelessly to make publishing happen. We are glad you wanted to share your experiences with us because, without any doubt, teachers are an important part of the teaching processes because what teachers say and do impact students’ lives.